Mental Health Effects in Primary Care Patients 18 Months After a Major Wildfire in Fort McMurray: Risk Increased by Social Demographic Issues, Clinical Antecedents, and Degree of Fire Exposure - Moosavi, Shahram; Nwaka, Bernard; Akinjise, Idowu; Corbett, Sandra E.; Chue, Pierre; Greenshaw, Andrew J.; Silverstone, Peter H.; Li, Xin-Min; Agyapong, Vincent I. O. (Frontiers in Psychiatry, 2019)
Objectives: To assess prevalence of likely Post-Traumatic Stress Disorder (PTSD), Major Depressive Disorder (MDD), and Generalized Anxiety Disorder (GAD) in patients attending the only out-of-hours primary care clinic in Fort McMurray some 18 months following a major fire. Methods: A quantitative cross-sectional survey was used to collect data through self-administered paper-based questionnaires to determine likely PTSD, MDD and GAD using the PTSD Checklists for DSM 5, PHQ 9 and GAD-7 respectively from residents of Fort McMurray who were impacted by the wildfires. This was carried out eighteen (18) months after a major wildfire which required the rapid evacuation of the entire city population (approximately 90,000 individuals). Results: We achieved a response rate of 48% and results from the 290 respondents showed the one month prevalence rates for likely PTSD was 13.6%, likely MDD was 24.8%, and likely GAD was 18.0%. Compared to self-reported prevalence rates before the wildfire (0%, 15.2%, and 14.5% respectively) these were increased for all diagnoses. After controlling for other factors in a logistic regression model, there were statistically significant associations between individuals who had likely PTSD, MDD and GAD diagnoses and multiple socio-demographic, clinical, and exposure-related variables as follows:. PTSD: History of Anxiety Disorder and received counselling had Odds Ratios (ORs) of 5.80 and 7.14 respectively. MDD: Age, witnessed the burning of homes, history of Depressive Disorder and receiving low level support from friends and family had ORs of 2.08, 2.29, 4.63 and 2.5 respectively. GAD: Fearful for their lives or the lives of friends/family, history of Depressive Disorder, and history of Anxiety Disorder had odds ratios of 3.52, 3.04, and 2.68 respectively. There were also associations between individuals with a likely psychiatric diagnosis and those who also had likely alcohol or drug abuse/dependence. Conclusion: Our study suggests there are high prevalence rates for mental health and addiction conditions in patients attending the out-of-hours clinic 18 months after the wildfires, with significant associations between multiple variables and likely PTSD, MDD and GAD. Further studies are needed to explore the impact of population based mental health interventions on the long term mental health effects of the wildfires.